Fluid–Solid Mixing Transfer Mechanism and Flow Patterns of the Double-Layered Impeller Stirring Tank by the CFD-DEM Method - Man Ge; Gaoan Zheng (Energies, 2024)
The optimization design of the double-layered material tank is essential to improve the material mixing efficiency and quality in chemical engineering and lithium battery production. The draft tube structure and double-layered impellers affect the flow patterns of the fluid–solid transfer process, and its flow pattern recognition faces significant challenges. This paper presents a fluid–solid mixing transfer modeling method using the CFD-DEM coupling solution method to analyze flow pattern evolution regularities. A porous-based interphase coupling technology solved the interphase force and could be used to acquire accurate particle motion trajectories. The effect mechanism of fluid–solid transfer courses in the double-layered mixing tank with a draft tube can be obtained by analyzing key features, including velocity distribution, circulation flows, power, and particle characteristics. The research results illustrate that the draft tube structure creates two major circulations in the mixing transfer process and changes particle and vortex flow patterns. The circulating motion of the double-layered impellers strengthens the overall fluid circulation, enhances the overall mixing efficiency of the fluid medium, and reduces particle deposition. Numerical results can offer technical guidance for the chemical extraction course and lithium battery slurry mixing.